2011
DOI: 10.1001/archgenpsychiatry.2011.91
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Early Trauma Exposure on Serotonin Type 1B Receptor Expression Revealed by Reduced Selective Radioligand Binding

Abstract: Context Serotonergic dysfunction is implicated in the pathogenesis of posttraumatic stress disorder (PTSD), and recent animal models suggest that disturbances in serotonin type 1B receptor function, in particular, may contribute to chronic anxiety. However, the specific role of the serotonin type 1B receptor has not been studied in patients with PTSD. Objective To investigate in vivo serotonin type 1B receptor expression in individuals with PTSD, trauma-exposed control participants without PTSD (TC), and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 96 publications
(149 reference statements)
1
66
0
Order By: Relevance
“…As the mechanisms of development are under both genetic and environmental control, studies in monkeys and rodents support the important role of gene-environment interactions in the etiology of anxiety [3]. Indeed, genetic variations in the promoter of the serotonin transporter gene [4], changes in the expression of the serotonin type 1B receptor [5] or a decrease in hippocampal volume [6] have been related to individuals more likely predisposed to develop anxiety disorders and depression when exposed to traumatic experiences. …”
Section: Anxiety Disorders and Bdnfmentioning
confidence: 99%
“…As the mechanisms of development are under both genetic and environmental control, studies in monkeys and rodents support the important role of gene-environment interactions in the etiology of anxiety [3]. Indeed, genetic variations in the promoter of the serotonin transporter gene [4], changes in the expression of the serotonin type 1B receptor [5] or a decrease in hippocampal volume [6] have been related to individuals more likely predisposed to develop anxiety disorders and depression when exposed to traumatic experiences. …”
Section: Anxiety Disorders and Bdnfmentioning
confidence: 99%
“…This system works in concert with various environmental and endogenous signals such as day light intensity and length and several hormones as cortisol , progesterone and dehydroepiandrosterone sulfate . Furthermore, it has shown an integral role in the pathophysiology of common neuropsychiatric disorders including major depression (Mann, 1999;Staley et al, 1998), bipolar disorder (Chee et al, 2001), obsessive compulsive disorder (Adams et al, 2005), anxiety disorders (Akimova et al, 2009;Lanzenberger et al, 2007;van der Wee et al, 2008), post-traumatic stress disorder (Davis et al, 1997;Murrough et al, 2011aMurrough et al, , 2011b, eating disorders (Bailer et al, 2005;Mayer and Walsh, 1998), sleep disturbance (Portas et al, 1998), attention deficit hyperactivity disorder (Quist et al, 2003), drug addiction (Carey et al, 2005;Muller et al, 2007), suicidal behavior (Mann, 1999), schizophrenia (Abi-Dargham, 2007;Aghajanian and Marek, 2000;Hurlemann et al, 2005;Hurlemann et al, 2008), Alzheimer (Ouchi et al, 2009), migraine (Panconesi, 2008) and epilepsy (Assem-Hilger et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition pre-clinical behavioural pharmacology studies (Sari, 2004), and more recently human positron emission tomography (PET) studies suggest a role for 5-HT 1B in the aetiology and treatment of post-traumatic stress disorder (Murrough et al, 2011), whilst genetic studies have suggested an association between 5-HT 1D and anorexia nervosa (Bergen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 C] WAY100635 in particular has been used to aid early drug development by defining the relationship between administered dose and 5-HT 1A receptor occupancy (Rabiner et al, 2000(Rabiner et al, , 2002. More recently, a number of PET radioligands have become available for 5-HT 1B : [ 11 C]P943 (Nabulsi et al, 2010) and [ 11 C]AZ10419369 (Varnas et al, 2011). However, these ligands were not available to us at the time our study was conducted.…”
Section: Introductionmentioning
confidence: 99%